BUSINESS REPUTATION AND SOCIAL MEDIA: THE DEVELOPMENT OF A MARKETING STRATEGY BASED ON THREATS TO THE ENTERPRISE - D. Golovanova (Вестник университета)
With the emergence of the Interactive Web or (Web 2.0), social media applications gained enormous popularity among Internet users forcing businesses to adapt their marketing strategies to incoming threats. Various response strategies are classified according to the source of the reputation threat.